2009
DOI: 10.1128/ec.00050-09
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Signaling Networks Regulating Fungal Morphogenesis by Transcriptomics

Abstract: Coordinated control of hyphal elongation and branching is essential for sustaining mycelial growth of filamentous fungi. In order to study the molecular machinery ensuring polarity control in the industrial fungus Aspergillus niger, we took advantage of the temperature-sensitive (ts) apical-branching ramosa-1 mutant. We show here that this strain serves as an excellent model system to study critical steps of polar growth control during mycelial development and report for the first time a transcriptomic fingerp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 107 publications
0
50
0
Order By: Relevance
“…Transcriptomics work on A. niger SSF is limited and the situation for Aspergillus biofilms is minimal but interesting work was published on SCF for several features [92][93][94][95][96]. Some results obtained with A. fumigatus biofilms have been already discussed elsewhere [1].…”
Section: Transcriptomicsmentioning
confidence: 94%
“…Transcriptomics work on A. niger SSF is limited and the situation for Aspergillus biofilms is minimal but interesting work was published on SCF for several features [92][93][94][95][96]. Some results obtained with A. fumigatus biofilms have been already discussed elsewhere [1].…”
Section: Transcriptomicsmentioning
confidence: 94%
“…Its product functions as a chitinase involved in cell wall remodeling and/or maturation (Yamazaki et al, 2008). During branching of A. niger hyphae, gene An09g06400 was downregulated (Meyer et al, 2009). Differential regulation of these genes suggests that the presence of Collimonas promotes changes in fungal cell wall dynamics, some of which are likely to be linked to the changes in hyphal morphology (Figure 2b).…”
Section: Cell Wallmentioning
confidence: 99%
“…It has recently been shown that it is also present and functional in the filamentous fungus A. niger Meyer et al, 2010). In A. niger, it has been shown that a single point mutation in the RmsA gene is responsible for defective hyphal growth, suggesting its involvement in the elongation rate of the parent hypha prior to the appearance of apical branches ( Reynaga-Peña andBartnicki-Garcia, 2005 andMeyer et al, 2009). The RmsA gene is also present in the T. melanosporum genome and the alignment with the ortholog proteins of yeast and A. niger has allowed us to confirm the presence of the conserved domains.…”
Section: Hyphal Growth Machinery and Its Transcriptional Regulationmentioning
confidence: 82%